Effective Septal Extension Graft for Asian Rhinoplasty - Jae Hoon Kim; Jin Woo Song; Sung Wan Park; Won Suk Oh; Joo Heon Lee (Archives of Plastic Surgery, 2014)
Background This study aimed at overcoming the disadvantages of septal extension grafts and keeping the nasal tip as natural as possible by using different forms of the graft and additional supporting methods depending on the case. Methods Among 458 patients who received a septal extension graft from March 2008 to September 2011, 107 patients were selected who underwent at least a 6-month follow-up. Patients were categorized according to the primary objective of the operation; an upturned tip correction or tip lengthening, tip lengthening with tip projection, or retracted columella correction. Each group of patients received a different type of septal extension graft out of 3 different types of grafts based on the purpose of the operation. The evaluation of the results was made from by comparing preoperative and postoperative photographs of the tip angle, projection, and nasolabial angle. Results The average tip angle for the patients in the upturned tip correction group was reduced to 98.3 from 124.9 degrees. For the patients in the tip lengthening with tip projection group, the average tip angle was reduced to 96.8 from 122.4 degrees and the average tip projection was increased to 27.5 from 23.2 mm. The average nasolabial angle for the patients in the retracted columella correction group was increased to 94.6 from 74.8 degrees. Conclusions Sufficient nasal tip lengthening and projection could be achieved by applying a septal extension graft using the graft best suited for the group of patients categorized by surgical objective.